Dihydromyricetin protects HUVECs of oxidative damage induced by sodium nitroprusside through activating PI3K/Akt/FoxO3a signalling pathway. Issue 7 (21st May 2019) - Zhang, Xiaoying; Wang, Lifang; Peng, Lizhi; Tian, Xiaoying; Qiu, Xiaoyuan; Cao, Huan; Yang, Qiaohong; Liao, Rifang; Yan, Fengxia
Abstract: The damage of vascular endothelial cells induced by oxidative stress plays an important role in the pathogenesis of atherosclerosis. Dihydromyricetin (DMY) is considered as a natural antioxidant. However, the mechanism of DMY on endothelial cell injury induced by oxidative stress remains unclear. In this study, we found that DMY could reduce the oxidative damage of HUVECs induced by sodium nitroprusside (SNP), HUVECs pre‐treated with DMY suppressed SNP‐induced apoptosis by reduced ROS overproduction of intracellular, decreased MDA level and elevated the superoxide dismutase activity. Meanwhile, we found that DMY could promote the expression of phosphorylated FoxO3a and Akt, and affect the nuclear localization of FoxO3a, when treated with the PI3K inhibitor LY294002, the effect of DMY was blocked. These data suggest that DMY protects HUVECs from oxidative stress by activating PI3K/Akt/FoxO3a signalling pathway. Therefore, DMY may have great therapeutic potential as a new drug for atherosclerosis.